Effects of a character education program integrating community service-learning on nursing students: a quasi-experimental study - Nayoung Kim (BMC Nursing, 2026)
Abstract Background Nursing demands a high level of character and personal qualities. However, high school students in South Korea have primarily received exam-focused education rather than character development. After entering university, they become vulnerable to challenges in character development due to academic pressure and stress. This study developed a character education program integrating community service-learning for nursing students and evaluated its effects on character, satisfaction with one’s major, happiness, and problem-solving skills. Methods This quasi-experimental study employed a nonequivalent control group pretest-posttest. The study was conducted at a university in South Korea. The participants were divided into an experimental group ( n = 30) and a control group ( n = 30). Overall, 60 nursing students participated. The character education program was designed with a focus on the moral virtues essential for nurses, incorporating nursing education and service-learning through self-directed team project activities. The character education program was developed based on Lickona’s theory of character education, the ADDIE model, and the core elements of service-learning, including reflection and reciprocity. Results Compared with the control group, the experimental group showed significantly higher post-intervention scores in character (t = 3.01, p =.004), satisfaction with one’s major (t = 2.66, p =.010), happiness (t = 4.52, p < 0.001), and problem-solving skills (t = 2.56, p =.013). Within the experimental group, all four outcome variables significantly increased after the intervention. Among the character subdomains, significant post-intervention differences between the two groups were observed in ethical consciousness, responsibility, respect, self-regulation, positive self-understanding, and consideration/service, whereas no significant between-group differences were found in career planning or competence/volition. Conclusion This program effectively integrated nursing education, character development, and community service-learning. The findings showed that the program contributed to improvements in nursing students’ character, satisfaction with one’s major, happiness, and problem-solving skills. These findings suggest that the program can be effectively utilized in academic and community-based nursing education settings.